2021
DOI: 10.26650/eor.2021869185
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of dental students towards online education during the covid-19 pandemic

Abstract: PurposeThis study evaluated the usage habits, attitudes, and perceptions of undergraduate dental students toward distance (online) learning and identified variables related to those attitudes. Materials and MethodsThe study included 1,605 undergraduate dental students who participated voluntarily. The data collection tool consisted of a distance learning attitude scale, a questionnaire on personal information, and open-ended questions. The perceptions of dental students to distance education according to the y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 30 publications
(43 reference statements)
1
16
0
4
Order By: Relevance
“…This concurs with the results by Varthis & Anderson among dental students where positive perceptions of BL were reported [36]. In fact, numerous studies in the literature reported genrally positive attitudes of online tutorials among dental students [9,[20][21][22]. This indicates that BL has a strong potential to be the accepted method of education among dental students in the future.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…This concurs with the results by Varthis & Anderson among dental students where positive perceptions of BL were reported [36]. In fact, numerous studies in the literature reported genrally positive attitudes of online tutorials among dental students [9,[20][21][22]. This indicates that BL has a strong potential to be the accepted method of education among dental students in the future.…”
Section: Discussionsupporting
confidence: 90%
“…The difference was statistically significant (p-value < 0.05). Comparatively, Gungor et al found that online learning was more preferred by the senior students and attributed that to the fact that younger students may have difficulty understanding and following online lessons as they have not acquired enough background in the field [9].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Obviously, it would have been useful to specify how many dental institutions exist in Egypt and how many dental clinical students were targeted in this study to better appreciate the representativeness of the sample. In Turkey for example, 65 dental schools currently exist, involving 13 private and 52 state universities (Sarialioglu Gungor et al, 2021 ), while in Tunisia there is only one public dental faculty for the country. The total number of dental faculties in a country should be mentioned to better evaluate the study.…”
mentioning
confidence: 99%